Answer:
y = [tex]\frac{1}{2}[/tex] x - 2
Step-by-step explanation:
the equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y-intercept )
rearrange 2x + y = - 6 into this form
subtract 2x from both sides
y = - 2x - 6 ← in slope-intercept form
with slope m = - 2
given a line with slope m then the slope of a line perpendicular to it is
[tex]m_{perpendicular}[/tex] = - [tex]\frac{1}{m}[/tex] = - [tex]\frac{1}{-2}[/tex] = [tex]\frac{1}{2}[/tex]
y = [tex]\frac{1}{2}[/tex] x + c ← is the partial equation
to find c substitute (6, 1) into the partial equation
1 = 3 + c ⇒ c = 1 - 3 = - 2
y = [tex]\frac{1}{2}[/tex] x - 2 ← equation of perpendicular line